1976
DOI: 10.1210/endo-98-4-859
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and Estrogen Control of Uterine Prostaglandin Dehydrogenase Activity During Deciduomal Growth

Abstract: Prostaglandin, dehydrogenase activity was determined in deciduomal and myometrial tissues during growth and regression of the deciduoma during pseudopregnancy. The hormonal control of prostaglandin dehydrogenase activity in these tissues was determined in experiments with ovariectomized pseudopregnant rats. Prostaglandin dehydrogenase activity for both prostaglandin E1 (PGE1) and prostaglandin F2alpha (PGF2alpha) in deciduomal and myometrial tissues increased during the growth of the deciduoma and decreased du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The present results may be combined with those reported previously for progesterone effects on PGDH (16,(42)(43)(44)(45), to develop a scheme by which PGDH expression and activity in chorion and placental trophoblasts may reflect a balance between opposing influences of cortisol and progesterone (Fig. 5, A and B).…”
Section: Discussionsupporting
confidence: 73%
“…The present results may be combined with those reported previously for progesterone effects on PGDH (16,(42)(43)(44)(45), to develop a scheme by which PGDH expression and activity in chorion and placental trophoblasts may reflect a balance between opposing influences of cortisol and progesterone (Fig. 5, A and B).…”
Section: Discussionsupporting
confidence: 73%
“…In our results, the white matter properties of the cingulum bundle during the periovulatory phase were significantly correlated with the intensity of menstrual pain as rated by patients during the subsequent menstrual period. As we know, one of the main factors responsible for the pathogenesis of PD is the overproduction of uterine PGs [Dawood, ] which are controlled by both estrogen and progesterone [Alam et al, ; Castracane and Jordan, ]. Animal studies demonstrated that estrogen and progesterone could stimulate neurite outgrowth, synapse number, dendritic branching and myelination [Cooke and Woolley, ; Sá et al, ], forming the basis of white matter connectivity in the central nervous system [Peper et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…PGDH is high in secretory phase endometrium and probably never falls in a pregnant cycle and is certainly high in early pregnancy decidua (Keirse and Turnbull, 1975;Keirse, 1985). PGDH may be under progesterone control (Casey et al, 1980;Alam et al, 1975;Falkay and Sas, 1987;Bedwani and Marley, 1975) and it is not surprising that RU486 reduces the activity of this enzyme, which has a short half-life (Xun et al, 1991), and thus is well placed as a key controller of prostaglandin concentration. The result of a decrease in PGDH activity would be both an increase in sensitivity to exogenous prostaglandin (Swahn and Bygdeman, 1988), because of reduced catabolism, and an increased effectiveness of prostaglandin produced within the amnion or decidua (Mitchell et al, 1978).…”
Section: Discussionmentioning
confidence: 99%